PEMBELAJARAN LITERASI KEUANGAN DENGAN PENDEKATAN METODE KONMARI PADA GENERASI Z DI PONDOK PESANTREN DARUL QURAN MOOSALAMTI, KOTA GORONTALO - Pongoliu, Yayu Isyana D (Ahsan Mafaza Indonesia, 2023)
Financial literacy is one of the knowledge and abilities that the younger generation, especially Gen Z, must have because they will be the demographic bonus in the future. Gen Z who have a good level of financial literacy will be able to have good financial management so that they can achieve financial stability and security which will also have an impact on the community's economy. Moosalamati Islamic Boarding School is one of the educational institutions that prepares the younger generation, so it is important to equip its students with financial literacy. Financial literacy education with an approach that adopts the Konmari method can be used as a tool to introduce financial literacy to students in a more interesting way according to the characteristics of Gen Z. The methods used in this service are lectures, discussions and practice. The results showed that the majority, namely 97%, were able to practice setting financial priorities based on the Konmari method. However, based on the post-test results, only 29% could understand financial literacy using the Konmari method approach comprehensively.